GENERAL CHARACTERISTIC OF THE SYSTEM OF WORD-FORMATION ADVERBS IN DIALECT COSSACKS-NEKRASOVTSEV - Violetta Mikhailovna Gryaznova (Вестник Северо-Кавказского федерального университета)
The article is devoted the description of world-building features adverb nomination of Cossack- Nekrasovtsev dialect.